Anaesthetic hypersensitivity reactions in France between 2011 and 2012: the 10th GERAP epidemiologic survey. Issue 3 (March 2017) - Tacquard, C.; Collange, O.; Gomis, P.; Malinovsky, J.‐M.; Petitpain, N.; Demoly, P.; Nicoll, S.; Mertes, P. M.
Abstract : Background: Immediate hypersensitivity reactions during anaesthesia are rare but potentially life‐threatening. The epidemiology changes with time and evolving professional practice, and hence needs to be monitored. Our objective was to follow this epidemiology. Methods: This was a retrospective, observational study in French hospital clinics, conducted by GERAP members (Groupe d'Étude des Réactions Anaphylactoïdes Périopératoires). Consecutive patients seen in allergo‐anaesthesia outpatient clinics, who had experienced a hypersensitivity reaction during anaesthesia between 1 January 2011 and 31 December 2012, were included. Demographic data, allergy history, drugs received before the reaction, symptoms of the reaction, results of blood samples (histamine, tryptase, IgE‐specific assays), and results of the allergy assessment were recorded. Results: The most common causes of allergic reactions were (Neuromuscular Blocking Agents) NMBAs ( N = 302; 60.6%), antibiotics ( N = 91, 18.2%, Cephalosporin N = 49, 10%) and dyes ( N = 27; 5.4%). Latex as an allergic agent was involved in 26 cases (5.2%), hypnotics in 11 cases (2.2%) and opioids in seven cases (1.4%). Of the NMBAs, Rocuronium had the highest proportion of reactions (13.8 reactions/100, 000 vials sold) followed by Suxamethonium (13.3/100, 000 vials sold). Cisatracurium had the lowest proportion of reactions (0.4/100, 000 vials sold). Patients were sensitized to two or more NMBAs in 48.9% of cases and without testing, cross‐sensitivity cannot be predicted. Conclusions: When compared with the previous GERAP studies, NMBAs are still the most frequently triggering allergens, with marked differences between individual NMBAs, but they are now followed by antibiotics (of which greater than 50% were cephalosporins) and dyes. Anaesthetists must be aware of the differences between drugs and of the pattern of emerging allergens. For the future of safe anaesthesia, allergy assessment is essential.